The use of unmanned aerial vehicle (UAV) for inventory and assessment of the experimental plantation in Lisino training and experimental forest of Saint-Petersburg State Forest Technical University. (August 2019) - Alekseev, A; Danilov, Yu; Nikiforov, A; Guzuk, M; Kireev, D
Abstract: In the article results of experimental plantation assessment and inventory made by UAV are presented. Plantation parameters such as the area, the length of the rows with planted trees, number of planted trees and trees heights was assessed both on ground and remotely. The aim of the research was to estimate systematic and random errors of estimations done by remote sensing method. The high resolution aerial photograph of the plantation established by 1997 was done by Geoscan 101 UAV. PhotoScan software was used for photogrammetric treatment of the obtained image. Multilevel special GIS was developed for plantation parameters calculations. As a result of the plantation parameters measurements made by remote sensing and ground method the following systematic and random errors was revealed: row length – systematic error as much as -6.9 meters, random 7.39 meter; trees height – systematic error as much as 0.4 meter, random 1.24 meter; number of trees – no any error. Taken into account the accuracy of used on UAV GPS positioning device which is as much as ±10 meter and also accuracy of ground measurements which was as much as ±5 meter we may conclude that remotely determined by using UAV plantation parameters are enough accurate and precise.